Hubungan Kecanduan Media Sosial dengan Phubbing dalam Situasi Classical pada Mahasiswa di Kota Padang - Mu’adzah, Hanifah Alya; Rusli, Devi (YASIN, 2024)
This research aims to determine the relationship between social media addiction and phubbing in a classical situation among students in Padang City. This research uses a quantitative approach with correlational methods. The sample was selected as 275 students using purposive sampling technique. This research was conducted on a number of students in Padang City using a generic scale of phubbing measuring instrument adapted from Isrofin (2020) with 15 items from 4 aspects and a social media addiction measuring instrument adapted from Agung & Sahara, (2023) with 15 items from 3 aspects. Data analysis in this research uses product moment correlation techniques. The results of this research show that there is a high correlation between social media addiction and phubbing in classical situations among students in Padang City. It was concluded that the higher the level of social media addiction among students, the higher the level of phubbing behavior that appears. On the other hand, if students' social media addiction is at a low level, the lower the level of phubbing behavior that appears.